The inter-temporal relationship between risk, capital and efficiency: ‎Evidences from Iranian Banks - Somayeh Yarifard; Ali Asghar Salem; Teymour Mohammadi; Abbas Shakeri (اقتصاد باثبات, 2023)
The increase in concentration in the banking sector, along with the problems of the recent financial and economic crises, has shown the importance of banking regulations against the high risk caused by the imbalance in the banks' balance sheets and one of the basic measures in the development of banks is to increase the efficiency of these financial institutions. Therefore, efficiency in banks always has been a matter of attention, and the weakness of the banking system can be a serious threat to the stability of the macro economy. In this way, banks with their credit operations and financing for different economic sectors, they provide suitable conditions for investment and cause the increase and growth of capital and finally the national production.The aim of the current research is to inter temporal relationship between risk, capital and efficiency in Iran's banking system. For this purpose, the data of Iran's commercial and specialized banks have been collected during the years 2006 to 2019 and to evaluate the model, In order to measure the model, the efficiency of banks has been estimated using the stochastic frontier model (SFA), Then, the relationship between risk, efficiency and capital is investigated using the seemingly unrelated regression (SUR) approach. In total, the obtained results show the existence of a relationship between capital and efficiency with risk. The results indicated that with the increase in the capital ratio, the risk of banks decreases and also increasing efficiency increases risk, also with the increase in the internal rate of return of banks, the capital ratio increases and Increasing the size of the bank increases efficiency.Extended AbstractIntroductionAs important financial institutions, banks are the basis for the prosperity of financial markets and economic growth by reducing the information gap and uncertainty in the capital market. Today, due to the huge changes that have taken place in economic structures and financial systems, the role of banks as an influential factor in the economy has become more prominent and important than before. In fact, the nature of banks' activity is such that although they do not show signs of crisis or bankruptcy on the surface, they can carry hidden crises with them in different forms and these crises have caused the officials of the regulatory and executive institutions of the financial systems to consider the risk management of such financial institutions and the factors affecting their risk level more seriously and expertly than before (Asayesh, 2015). The aim of the current research is to inter temporal relationship between risk, capital and efficiency in Iran's banking system.MethodologyTo calculate the efficiency of banks as service units, there are two approaches; first, a bank that has a high efficiency can produce more products than other banks with a set of assumed and fixed data. In this definition, there is a discussion on changing the amount of production and it is called product-oriented efficiency. Second, the ratio of the minimum possible cost to the cost realized to provide a certain amount of service or output is considered compared to all the units that exist in that industry, which is called the input-oriented approach.Considering the integration and application of the efficiency variable in an econometric model and the preference of the SFA estimation method in the literature that examines the relationship between capital, risk and efficiency, in this research the stochastic frontier function method has been used to estimate the efficiency levels of the banking system (Emami Meybodi,2000). In this research, inter-temporal relationship means examining the relationship between variables based on time trends. This relationship is examined based on the empirical studies of Kwan and Isenbis in 1995, Jensen in 1986, Williams in 2003 and Michalski in 2007, within the framework of the following system of simultaneous equations:    Resultsthe data of Iran's commercial and specialized banks have been collected during the years 2006 to 2019. The results of the model estimation are presented in the following table:The results of estimation of the modelEFF CAPRISK P>|z|CoefficientP>|z|CoefficientP>|z|CoefficientVariable0.070.33230.00-0.1125--Risk0.001.1096--0.01-0.3635Cap0.080.05480.98-0.00010.050.0081Size0.08-0.26950.250.03110.810.0149Tpbt0.00-0.0009----Obsta--0.001.4447--Roa----0.10.0005Nlta--0.000.04940.060.0429Eff0.001.18380.56-0.02310.17-0.1117ConsSource: research findingsAccording to the significance level of the Risk model, it can be seen that only the coefficient of the capital ratio variable has a significant difference from zero at the 5% error level and the cost efficiency variable has a significant difference from zero at the 10% error level. In the estimated model, the capital ratio variable has a coefficient of -0.363, based on which, assuming the stability of other conditions, a one percent increase in the capital ratio has led to a 0.363 percent decrease in the bank's risk. The results of the CAP model show that the coefficient of risk variables, roa and cost efficiency has a significant difference from zero at the 5% error level. In the estimated model, the risk variable has a coefficient of -0.112, based on which, assuming the stability of other conditions, a one percent increase in the bank's risk has led to a decrease of 0.112 percent in the bank's capital. In the EFF model, the results show that the coefficient of capital variables and off-balance sheet items to total assets has a significant difference from zero at the 5% error level, and the risk variable has a significant difference from zero at the 10% error level.The aim of the current research is to inter temporal relationship between risk, capital and efficiency in Iran's banking system. For this purpose, the data of Iran's commercial and specialized banks have been collected during the years 2006 to 2019 and to evaluate the model, In order to measure the model, the efficiency of banks has been estimated using the stochastic frontier model (SFA), Then, the relationship between risk, efficiency and capital is investigated using the seemingly unrelated regression (SUR) approach. In total, the obtained results show the existence of a relationship between capital and efficiency with risk. The results indicated that the increase in the capital ratio, lesds to decrease the risk of banks and also increasing the efficiency leads to risk increasing. also with an increase in the return on assets of banks, the capital ratio increases and Increasing the size of the bank increases efficiency.Ethical ConsiderationsFunding: The authors did not receive any financial resources for the research, writing and publication of this articleAuthors’ contribution: The present article is taken from the doctoral dissertation of Somayeh Yarifard with Supervisor of Ali Asghar Salem at the University of Allameh Tabataba.Conflict of interest: The authors of the article declare that there is no conflict of interest in publishing the presented article.Acknowledgments: We appreciate all the people and institutions that helped the author in conducting this research.